PENGGUNAAN DANA DESA DALAM PRESPEKTIF MAQASHID SYARIAH - Maylalang Syahputri, Inkha (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
Abstract The state has an important role in the development of a region. The regional development can be carried out through various aspects of education so that in order to achieve this development the state gives a separate authority or regional autonomy, one of which is in the rural area. Village financial management is an integral part of the state and regional financial system. This research was conducted in Grogol Village, Tulangan District, Sidoarjo Regency by using a qualitative approach with the comparison of maqashid syariah.